Automatic Coastline Detection Using Coastsat Toolbox and GIS: A Case Study at Oued-Laou Beach, Morocco - Souiri Smail; Hakkou Mounir; Haddaoui Hatim; Oubdil Soufiane; Lmrimed Nargiss (E3S Web of Conferences)
Coastal zones are vital ecosystems increasingly impacted by erosion and human activities. Accurate and timely shoreline mapping is essential for understanding coastal dynamics, predicting erosion, and guiding sustainable management strategies. This study presents an automatic approach for coastline detection using the CoastSat toolbox and GIS tools, applied to Oued-Lou Beach, Morocco. By analyzing publicly available satellite imagery spanning over 30 years, the study generated detailed coastline maps over a 23-year period, revealing significant spatial and temporal variations in shoreline changes. Analysis with the Digital Shoreline Analysis System (DSAS) showed significant erosion along the entire coastline, with the most severe erosion observed around the mouth of Oued-Laou, where erosion rates exceeded -2 m/year. In contrast, the northern sector experienced alternating periods of accretion (up to 0.5 m/year) and moderate erosion (around -0.5 m/year). The southern sector showed accretion rates ranging from 0.5 m/year to 1 m/year, while the area between OL5 and Cap Targha exhibited substantial erosion exceeding -1 m/year. These findings highlight the need for tailored management strategies to mitigate erosion and promote sustainable development in this coastal region.